1992
DOI: 10.1007/bf00180965
|View full text |Cite
|
Sign up to set email alerts
|

2-Methylsorbic acid, an antifungal metabolite of Penicillium vermiculatum

Abstract: 2-Methylsorbic acid (MA), (2Z,4E)-2-methyl-2,4-hexadienoic acid, is a new m e t a b o l i t e o f Penicillium vermiculatum. A n t i f u n g a l activity of this acid was higher than that o f sorbic acid or the b r o m o d e r i v a t i v e s brom o m e t h y l s o r b i c acid and b r o m o s o r b i c acid. M A suppressed the growth of Talaromyces flavus and germination o f its conidia. In P. vermiculatum this acid lowered p r o d u c t i o n of vermiculin and inhibited proteosynthesis in Saccharomyces cerevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Kim and Fravel (1990) showed that glucose oxidase produced by T. flavus prevented formation of microsclerotia of V. dahliae. However, Proksa et al (1992) showed that 2-methyl sorbic acid secreted by T. flavus showed an inhibitory effect on the growth of V. a.-a.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Fravel (1990) showed that glucose oxidase produced by T. flavus prevented formation of microsclerotia of V. dahliae. However, Proksa et al (1992) showed that 2-methyl sorbic acid secreted by T. flavus showed an inhibitory effect on the growth of V. a.-a.…”
Section: Discussionmentioning
confidence: 99%
“…The acid subunit was previously found as an ester of an antifungal compound isolated from Graphium putredinis (Kennedy et al, 1998) and the above-mentioned antifungal isomer (2Z, 4E) was identified as a free acid from culture extracts of Penicillium vermiculatum (Proksa et al, 1992). It is noteworthy that, although the strain grew well in the same medium without artificial sea water and also in malt extract agar, the compounds were not produced, even at trace levels, under those conditions.…”
Section: Resultsmentioning
confidence: 91%
“…Nonetheless, the acid 6 and the ester 5 displayed the greatest antifungal activity, in the same order as benomyl, a commercial antifungal product. The natural (2Z, 4E) isomer of 6 was previously reported as an antifungal metabolite against other fungal strains (Proksa et al, 1992). Several isoleucine derivatives were previously isolated from different microbial strains as C-amides (Kern et al, 1985), esters (Iwamoto et al, 1990) or unknowns (Kawakami et al, 1978).…”
Section: Resultsmentioning
confidence: 99%